The Influence of Capital, Use of Accounting Information and Entrepreneurial Characteristics on the Success of Culinary MSME Businesses in Rumbai District, Pekanbaru City - Basa Meilinda Manalu; Gusnardi Gusnardi; Mifta Rizka (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine whether there is an effect of capital, the use of accounting information and entrepreneurial characteristics on the success of culinary MSME businesses in Rumbai District, Pekanbaru City partially or simultaneously. This study uses primary data obtained directly from MSME owners in Rumbai District. Data collection techniques were carried out by observation, questionnaires and documentation. The sampling technique is using purposive sampling technique with a total sample of 30 businesses. Methods of data analysis using multiple regression. The classic assumptions used in this study are the normality test, multicollinearity test, heteroscedasticity test, t test and F test, the coefficient of determination and the regression equation. The results of this study indicate that the capital variable has no influence on the success of culinary MSME businesses in Rumbai District, Pekanbaru City. Variable use of accounting information and entrepreneurial characteristics have an influence on the success of culinary MSME businesses in Rumbai District, Pekanbaru City